High mobility n-type organic semiconductors with tunable exciton dynamics toward photo-stable and photo-sensitive transistors. Issue 22 (30th May 2022) - Yu, Li; Hu, Yongxu; Li, Jie; Wang, Zhongwu; Zhang, Haoquan; Huang, Yinan; Lou, Yunpeng; Sun, Yajing; Lu, Xueying; Liu, Huapeng; Zheng, Yingshuang; Wang, Shuguang; et al.
Abstract : High mobility n-type organic semiconductors with photo-stable and photo-sensitive characteristics. Abstract : Organic semiconductors (OSCs) are the material basis for various organic optoelectronics, where OSCs are required to possess different exciton dynamics characteristics. Therefore, designing high-mobility OSCs with tunable exciton dynamics toward photo-stable and photo-sensitive optoelectronic applications is of great significance for the organic electronics field. Herein, two novel n-type semiconductors with the same backbone and different halogen substituent groups (PQ-4FP and PQ-4ClP) are synthesized, both of which show excellent n-channel charge transport properties with the mobilities of 2.08 cm 2 V −1 s −1 (PQ-4FP) and 2.98 cm 2 V −1 s −1 (PQ-4ClP), respectively. Remarkably, single-crystal organic field-effect transistors (SC-OFETs) of PQ-4FP exhibit good photo-stability under the irradiation (white light) of 44.9 mW cm −2, while SC-OFETs of PQ-4ClP show good photo-sensitive characteristics. Through the analysis of the optical spectrum, it is proved that the photo-stability of PQ-4FP derives from the effective exciton–polaron quenching effect and the photo-sensitivity of PQ-4ClP comes from efficient exciton dissociation. This work provides a novel and efficient way to design high-mobility n-type OSCs and modulate their optoelectronic properties through molecular structure engineering.